Riglyne vir die toepassing in die onderrigleersituasie ten opsigte van tuberkulose - M Strydom; M Greeff; A Nel (AOSIS, 2000)
This article is a follow up article of the previoulsy published article "Die belewenis van die pasient en die verpleegkundige tydens tuberkulose-onderrig" and focuses on guidelines formulated on the basis of the research findings. These guidelines have been formulated in order to promote the nurse's knowledge and skills concerning: interpersonal relations, subject knowledge, a task versus patient orientated nursing approach, the motivation of the nurse, social support systems, stimulation of the patient's motivation, recovery from the patient's chest centredness and the acceptance of responsibility for his own health as well as the affirmation of the role of the nurse.